Kathā kukanusa dī - Ṭivāṇā, Dalīpa Kaura (Lokgeet Prakashan, 2001)
Novel, based on the lives of Indian immigrants living abroad.
A novel - Panjabi in Gurmukhi-Schr
Keywords: Pandschabi-Sprache; Roman; Indischer Einwanderer; Geschichte 2000-2100